Examining nursing practices for management of sepsis in low income countries: the case of Uganda - Aliga, Cliff; Mutyabule, Judith; Nakate, Grace; Emelonye, Abigail (The World of Critical Care Nursing, 2018)
A large amount of information about best practice standards in sepsis management is available for healthcare professionals; however, implementation and adherence to practice guidelines recommended by the Surviving Sepsis Campaign remains low in low income countries. A formal scope of practice for nursing and midwifery as a professional guideline is absent and national clinical guideline for Uganda remains unclear regarding the specific management of sepsis.Inadequate documentation of patient care in Uganda makes sepsis cases difficult to be early detected.Research evidence regarding sepsis management remainsscarce in Uganda. Adopting SSC guidelines without appropriate adaptation for the local context contributes problems, especially in LICs where necessary resources are limited.
Keywords: clinical guidelines; East Africa, nursing practice, sepsis management, Uganda